2016
DOI: 10.1519/jsc.0000000000001049
|View full text |Cite
|
Sign up to set email alerts
|

Novel Resistance Training–Specific Rating of Perceived Exertion Scale Measuring Repetitions in Reserve

Abstract: The primary aim of this study was to compare rating of perceived exertion (RPE) values measuring repetitions in reserve (RIR) at particular intensities of 1 repetition maximum (RM) in experienced (ES) and novice squatters (NS). Furthermore, this investigation compared average velocity between ES and NS at the same intensities. Twenty-nine individuals (24.0 ± 3.4 years) performed a 1RM squat followed by a single repetition with loads corresponding to 60, 75, and 90% of 1RM and an 8-repetition set at 70% 1RM. Av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
311
0
26

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 284 publications
(342 citation statements)
references
References 31 publications
5
311
0
26
Order By: Relevance
“…Then, based on established testing protocols [25], several sets of barbell back squats were performed until a load was found which the participants could lift exactly one time with a proper technique (stance width: shoulder width / squat depth: at least horizontal thighs). Between the testing sets, participants rested for at least three minutes and immediately after each set the perceived exertion was quantified using the Repetitions in Reserve scale (RIR) [26]. The RIR was used as countermeasure to verify that the 1-RM is the maximal load that the participants can lift.…”
Section: Methodsmentioning
confidence: 99%
“…Then, based on established testing protocols [25], several sets of barbell back squats were performed until a load was found which the participants could lift exactly one time with a proper technique (stance width: shoulder width / squat depth: at least horizontal thighs). Between the testing sets, participants rested for at least three minutes and immediately after each set the perceived exertion was quantified using the Repetitions in Reserve scale (RIR) [26]. The RIR was used as countermeasure to verify that the 1-RM is the maximal load that the participants can lift.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed to understand submaximal effort with this conceptualisation some studies have attempted to develop scales that assess effort during RT relative to MF. 21,22 However, a further consideration in this conceptualisation should also be the apparent difficulty people experience in differentiating between perceptions of effort and discomfort.…”
Section: Introductionmentioning
confidence: 99%
“…As noted, familiarization with the scale may be required and greater prior RT experience may improve its utility. The findings of other authors have suggested a higher accuracy in experienced participants (Steele et al, 2017a;Hackett et al, 2012;Hackett et al, 2016;Zourdos et al, 2016), especially when using higher loads (Zourdos et al, 2016). Indeed, predictive ability might be higher using higher loads, as discomfort was shown to be less in this case (Fisher, Farrow & Steele, 2017a;Stuart, Steele, Gentil, Giessing & Fisher, 2018).…”
Section: Discussionmentioning
confidence: 77%
“…Though rating of perceived effort (RPE) scales are widely employed in physical tasks such as sport and exercise, novel scales have been developed that are aimed at utilizing the feedback from increasing perceptions of fatigue and effort in order to predict proximity to task failure (Coquart et al, 2012;Helms et al, 2016). The application of predictions of proximity to task failure has been a particularly popular approach within resistance training in recent years to manipulate and control the intensity of effort employed in a given bout (Hackett, Johnson, Halaki & Chow, 2012;Hackett, Cobley, Favies, Michael & Halaki, 2016;Helms, Cronin, Storey & Zourdos, 2016;Zourdos et al, 2016). Considering the value of resistance training (RT) to improve physical fitness and health (Steele et al, 2017d), understanding the manipulation of variables such as effort within RT in order to maximize outcomes is of considerable interest.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation